Outpatient monitoring of patients with multisystem inflammatory syndrome (MIS-C): A mini review - Jose, Jerin Tresa; Selamet Tierney, Elif Seda (Frontiers in Pediatrics, 2022)
INTRODUCTION: As we learn more about the novel multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 infection, the protocols for long-term follow-up have evolved and only some of these protocols have been published. Here, we review the current literature on follow-up guidelines in MIS-C patients. METHODS: We conducted a PUBMED search of all articles published on “MIS-C” and the term “follow-up” between 2020 and 2022. Inclusion criteria were that (1) the study was an observational study or case series, and (2) the study population included pediatric population who met the diagnostic criteria for MIS-C. RESULTS: There were 206 publications on MIS-C and follow-up in the last two years with 11 studies that fit the inclusion criteria. These papers were representing 11 different centers and encompassed a total of 343 participants. Seven of the 11 studies had participants follow-up with their cardiologist within one month of discharge. Between 12-62% of patients within each study had depressed left ventricular ejection fraction (LVEF) at admission. At the initial follow-up visit, five studies showed a normal LVEF in all patients while the other seven studies showed 2-13% patients continuing to have depressed LVEF. In eight of the 11 studies, 9-52% of patients had coronary artery dilation at admission. At their initial follow-up visit, 3-28% of patients continued to have coronary artery dilation. CONCLUSION: There is some institutional variation in the outpatient follow-up protocols in patients diagnosed with MIS-C. A standardized follow-up guidelines might be helpful to monitor long-term prognosis of these patients.